Fabrication of nanomaterials-based solar cells - Kuek, Stephanie Yu Yan (2015)
Third Generation of Solar Cells have been researched intensively for many years as it has a latent potential to produce cheap and efficient photovoltaic cells by capturing a clean and renewable sunlight energy source. In this scientific report, it focuses on the fabricating Third Generation of Tandem Solar Cell by using PbSe Nano-Crystal Quantum Dots. This material is able to produce Multiple Exciton Generation (MEG) in the energy bandgap to enhance the efficiency of the solar cell. Tandem Solar Cell enables one to absorb a wide spectrum of sunlight range by stacking various semiconductors with different bandgaps. PbSe Nano-Crystal Quantum Dots will be the first active layer to absorb a range at the blue end of the solar spectrum while P3HT (Poly (3-hexlthiophene-2, 5diyl)) will be the second active layer to absorb a range at the red end of the solar spectrum. Different types of experiments are conducted in this scientific report. The first experiment uses PbSe Nano-Crystal Quantum Dots with Chloroform and the second experiment uses an additional compound of ZnCl2 added into the solution of PbSe Nano-Crystal Quantum Dots with Chloroform. The third experiment uses Pure PbSe Nano-Crystal Quantum Dot Solar Simulator to fabricate the Tandem Solar cell. Prober is then used to simulate the different types of Tandem Solar Cell to obtain the I-V characteristics curve. Analysis will be provided for the measurement of each experiment. Overall this scientific report focuses on the research of PbSe Nano-Crystal Quantum Dot Fabrication on the Tandem Solar Cell.